A Case of Subacute Combined Degeneration of the Spinal Cord with Infective Endocarditis - Xiao-Jiang Huang; Jia He; Wen-sheng Qu; Dai-Shi Tian (Case Reports in Neurological Medicine)
Background. Subacute combined degeneration (SCD) is a rare cause of demyelination of the dorsal and lateral columns of spinal cord and is a neurogenic complication due to cobalamin deficiency. Anemia of chronic disease (ACD) occurs in patients with acute or chronic immune activation, including infective endocarditis. It remains to be elucidated whether ACD patients are more sensitive to suffer from SCD. Little cases about SCD patients accompanied with ACD have been reported till now. Here we reported a 36-year-old man with SCD with a medical history of mitral inadequacy over 20 years, who was admitted and transported from another hospital to our hospital due to an 8-month history of gait disturbance, lower limb weakness and paresthesia, and loss of proprioception. Significant laboratory results and echocardiography suggest iron deficiency anemia and infective endocarditis (IE). The SCD diagnosis was confirmed by MRI, which showed selective demyelination in the dorsal and lateral columns of spinal cord. In conclusion, the ACD patients may suffer from SCD, which can be diagnosed by 3 Tesla magnetic resonance imaging.